The role(s) of intellectual property Rights for innovation: a review of the empirical evidence and implications for developing countries - Andréanne Léger (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The role patents play for innovation is not clear, but patenting activity has increased in the last decades. This article reviews the empirical evidence on traditional and novel roles of patents to assess their impacts on innovation in developing countries. It shows that patents are not likely to support innovation in developing countries, even though their non-traditional functions fulfill important roles. This questions the relevance of domestic patent systems, and indicates the need to reassess the costs and benefits of the patent system, the use of patents as innovation indicators, and the need for more research on developing countries.
Keywords: 330; Intellectual property rights; developing countries; innovation.; Patent; Innovation; Immaterialgüterrechte; Welt; Entwicklungsländer